Inclusion of Guar Gum and Alginate into a Crispy Bar Improves Postprandial Glycemia in Humans - Williams, Jennifer A.; Lai, Chron-Si; Corwin, Holly; Ma, Yingying; Garleb, Keith A.; Wolf, Bryan W.; Maki, Kevin C. (The Journal of nutrition, 2004)
A novel induced viscosity fiber (IVF) crispy bar was formulated with the viscous dietary fibers alginate and guar gum. To evaluate the glycemic response and gastrointestinal tolerance to IVF crispy bars, nondiabetic healthy adult subjects (n = 48) were studied in a randomized, double-masked, crossover design. The control crispy bars and IVF crispy bars were identical except for the 2 dietary fibers contained in the experimental (IVF) bars. After an overnight fast, subjects consumed test bars containing 50 g carbohydrate. Their capillary blood glucose response was determined for 180 min postprandially. When subjects consumed IVF, the incremental blood glucose excursions were reduced (P < 0.05) at 15, 30, 45, and 120 min. At 180 min, the subjects' blood glucose concentration was maintained above the basal blood glucose concentration for both bars. Compared with controls, the incremental peak blood glucose concentration was reduced (P < 0.001) 30% when subjects consumed IVF. When subjects consumed IVF, the positive incremental area under the curve for glucose was reduced (P < 0.01) by 33% compared with controls. In the 24-h postprandial period after each treatment, the frequency and intensity of gastrointestinal tolerance symptoms did not differ. In conclusion, compared with a control crispy bar, the IVF crispy bar attenuated the postprandial glycemic excursion without gastrointestinal intolerance in healthy adult subjects.